PROSEDUR PENYAJIAN DATA RADAR CUACA DAN DATA CURAH HUJAN - , ANDIKATAMA ANGGARA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is the country through which volcanic pathways. Frequent disasters, the volcanic eruptions, earthquakes, and debris flood. Equator also passes this country, so Indonesia has a tropical climate, where the properties of rain in the tropical climate concentrated in a relatively small area and keep moving from place to place. It would require dense rain graduated station, but with radar equipment, rainfall conditions can be monitoring, along with the intensity, and movement of rain areas from time to time with a wide range. Data which is obtained from the monitoring, functions for early warning, calculate of discharge, and planning waterworks. Radar weather EWR XD 700 is only specialized to monitor the rain clouds carrier. The radar transmits an electromagnetic wave to the target and will be reflected back by taking the distance information, the content of the rain, and the movement of clouds which will be processed to be a special rainfall data. Rainfall data is also obtained from rainfall section. Automatic rain gauge is widely used today with a recording system using a logger. Rainfall gauge and radar equipment supplementary. Radar monitors the cloud that is located in the atmosphere, while the gauge rainfall monitors when it rains, so that accurate data will be obtained if both devices are calibrated. Period of early warning for residents directly affected by the flood debris enough to evacuate.